Determination of Antibiotic Resistance Pattern and frequency of CTX-M, TEM, and SHV Β-Lactamase Encoding Genes among Shigella Isolates from Inpatients in Tehran, Iran - Shadi Beladi Ghannadi; Maryam Ghane; Laleh Babaeekhou (Medical Laboratory Journal, 2019)
ABSTRACT Background and Objectives: The emergence of extended-spectrum β-lactamase (ESBL)-producing Shigella spp. is becoming a health concern worldwide. This study aimed to investigate antibiotic resistance pattern and frequency of blaCTX-M, blaSHV, and blaTEM genes among Shigella isolates from patients in hospitals of Tehran, Iran. Methods: In this cross-sectional study, 52 non-repeated Shigella strains were isolated from hospitalized patients in Milad, Emam Khomeini and Shariati hospitals in Tehran (Iran) from November 2015 to December 2016. Bacterial identification, serotyping, and antimicrobial susceptibility testing were performed according to the standard guidelines. The blaCTX-M, blaSHV, and blaTEM resistance genes were identified using multiplex polymerase chain reaction. Results: Among 52 Shigella isolates, S. sonnei (44.2%) was the predominant species, followed by S. flexneri and S. dysenteriae (23%). Over 67% of the isolates were multidrug resistant. The highest rates of resistance were observed against cefalotin (67.3%), tetracycline (67.3%), amikacin (63.5%), trimethoprim-sulphamethoxazole (48.1), and ampicillin (42.3%). The lowest resistance rate was against ciprofloxacin (1.9%). We detected the blaTEM and blaCTX-M genes in 61.5% and 19.2% of the isolates, respectively. However, the blaSHV gene was not detected in any of the isolates. In addition, 16.4% of the isolates harbored the blaTEM and blaCTX-M genes simultaneously. Ciprofloxacin was the most effective antibiotics according to the ESBL genes distribution. Conclusion: Our findings indicate the high prevalence of multidrug resistance and ESBL genes in Shigella isolates, which elucidates the need for appropriate infection control measures for limiting the spread of resistant strains. Keywords: Shigella, Multiplex Polymerase Chain Reaction, Drug Resistance.